Motivation trajectories of Chinese L2 learners in a Sino-Canadian study-abroad program – a longitudinal study - LI, Lin (2020)
With the impetus for internationalized mobility and employability, a growing number of college students take part in variegated ‘study-abroad’ programs to improve second or foreign language competence. However, inconsistency in research findings and thus conclusions emerge in the literature investigating students’ motivation to learn an L2 during sojourns, triggering contestations and debates. The main cause of these inconsistent viewpoints largely roots in the complex and dynamic nature of motivation in the process of second language acquisition (SLA). Hence, the main aim of the study was to identify whether and how students’ L2 motivation change during the transition from their home culture settings of China to the host culture of Canada; to investigate whether there are any self-organized patterns underlying these changes; and to discover what kinds of factors and variables contribute to these changes and patterns. Based on the review of background literature in the areas of L2 motivation research and ‘study-abroad’ studies, a three-stage, mixed-method research was designed and developed, covering both quantitative and qualitative methods. The qualitative methods, such as interviews and learning blogs, were used to collect empirical data to investigate the dynamic and complex nature of Chinese college ‘study-abroad’ students’ L2 motivation. While focus was placed on the ‘study-abroad’ stage, the key findings were verified through large-scale questionnaires and further interviews prior to and post the students’ sojourns, and the triangulated data provided more reliable and dependable evidence of complexity and dynamicity in Chinese students’ L2 motivation. The research objectives were achieved. Firstly, both quantitative and qualitative data provided evidence for the changeable and complex nature of learners’ motivation to learn an L2 in the process of language acquisition. Besides, a variety of factors and variables were extracted which contributed to the complexity and dynamicity of L2 motivation, including learners’ motivational orientations and attitudes towards L2 learning, learners’ intrinsic psychological states and emotional feelings, language features of L2 learning and contextual factors in language learning environments. More importantly, these factors and variables revealed interactions among internal contextual processes as well as contextual processes in the external environments, indicating that from a Complex and Dynamic System (CDS) theory point of view, the interdependent relationship among the factors contributed to the complexity and dynamicity of L2 motivation in learning processes. With these achieved objectives, three distinct contributions to knowledge were identified, which made the present study significant and promising. Firstly, the study provided empirical evidence to support the Complex and Dynamic System theory in L2 motivation research. Secondly, it explored and identified the complex and dynamic nature of L2 motivation among those learners who transited from the home cultural setting to the host cultural setting. Lastly, it attempted to provide a systematic approach which might remove quantitative and qualitative boundaries in L2 motivation studies. In sum, by understanding the possible trajectories of L2 motivation, learners’ individual variables as well as interrelated contextual factors, the study presented a compelling, theory-driven explanation for how and why learners’ L2 motivation changed during the sojourn, and provided some theoretical, empirical and pedagogical implications for both researchers and practitioners to increase learners’ motivational level in the language learning processes.